THE CONCEPT OF HABIT FROM MERLEAU-PONTY’S THE STRUCTURE OF BEHAVIOR - dos Santos Beserra, Abel (2022)
This article seeks to answer how and if Merleau-Ponty presents a position on the concept of habit in The structure of behavior. Our hypothesis is that yes, although the philosopher almost does not address the concept directly throughout this text, because it is possible to extract consequences of his argumentation for the understanding of the category of habit. In this sense, we seek to substantiate our thesis both through the criticism of Merleau-Ponty directed at the idea of causality and from his concept of form. Thus, the habit is outlined as a behavior, more precisely as a form that describes the relationships through which the acts are learned and maintained over time. In this way, we defend that the concept of habit allows us to indicate how Merleau-Ponty criticizes and tries to overcome the reductionist conceptions of the science and of the philosophy.